School surrounding spaces and school operation: a perspective from the teaching staff - Caridade, Sónia (2019)
School is an importat agent of socialization and has drawn great attention to the scientific community to identify and characterize the main dimensions that may interfere with its operation and resulting academic performance of students. Collection of information about the school environment and surrounding spaces is an underlying dimension in school environment diagnostic reports development given its documented importance on crime prevention. It is important to understand not only school spaces distribution, but also surrounding spaces characteristics, namely, presence of stores/industry/services that may disturb its operation. School location, size, arquitecture, entrances and exits are important elements to be considered in deviant behaviour prevention. In an oral presentation, we seek to show some results from a research project being developed by education agents (teachers and staff), to analyse these professionals’ perspective on how the surrounding characteristics of spaces may influence school internal operation. This study intends to delineate, develop and implement action plans that may improve shcool operation and prevent problematic and/or antissocial behaviours in this context. Practical and preventive implications will be debated at the end.